Bond Strength of a total-etch adhesive at different post-bleaching with phthalimido peroxy caproic acid and tribarrel hydremide peroxide bleaching agents - Hugo, Jazmine S.; Medina III, Vicente O. (Department of Community Dentistry, University of the Philippines Manila, 2019)
Methodology: A total of 70 bovine incisors were used for this study. Flat 3 mm bonding substrate was produced by grinding initially using 240-grit Silicon Carbide (SiC) discs and finished with 600-grit SiC paper. The specimens were randomly assigned to 7 groups (n=10) namely: Total Etch (TE) adhesive resin bonded to 1. non-bleached enamel, 2. enamel bleached with bleaching agent containing phthalimido peroxy caproic acid (PAP) immediately after bleaching, 3. enamel bleached with bleaching agent containing PAP 1 day after bleaching, 4. enamel bleached with bleaching agent containing PAP 14 days after bleaching, 5. enamel bleached with hydremide peroxide (HP) immediately after bleaching, 6. enamel bleached with HP 1 day after bleaching, 7. enamel bleached with HP 14 days after bleaching. The TE adhesive and composite were manipulated following manufacturer?s instructions. The specimens were stored in distilled water for 1 day before shear bond strength (SBS) testing was performed using a universal testing machine with a crosshead speed of 1mm/minute.